Pelatihan Model Pembelajaran Inovatif dalam Rangka Meningkatkan Kompetensi Guru-Guru MGMP IPS SMP Wilayah Singaparna, Tasikmalaya - Suryani, Yeyen; Iskandar, Iskandar; Jumantini, Entin; Setiawan, Iyan; Pratiwi, Rani Tania; Mulyati, Sri (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2023)
So far, the learning model chosen by the teacher has not been able to provide opportunities for students to be involved in it through direct practice, teaching and applying the material that has been learned. Teachers often use conventional methods so that teachers tend to be more dominant in learning, on the other hand students tend to be passive, less critical and creative. The purpose of this community service is to provide new knowledge and insights to MGMP Social Studies teachers at Singaparna Junior High School, Sukahaji Village, Singaparna District, Tasikmalaya Regency about innovative learning models, so that their minds and competencies and motivations are open to them to have the ability to master various innovative learning models. . The method used in this activity is in the form of training through lectures, questions and answers and discussions. The result achieved is an increase in the understanding and knowledge of MGMP Social Studies teachers regarding innovative learning models and how to apply these innovative models. Selama ini model pembelajaran yang dipilih guru belum dapat memberikan kesempatan pada siswa untuk ikut terlibat didalamnya melalui praktik langsung, mengajarkan dan menerapkan materi yang telah dipelajari. Guru seringkali menggunakan metode konvensional sehingga guru cenderung lebih bersifat dominan dalam pembelajaran, di lain pihak siswa cenderung pasif , kurang kritis dan kreatif. Tujuan dari pengabdian masyarakat ini untuk memberikan ilmu dan wawasan baru kepada guru-guru MGMP IPS SMP Singaparna Desa Sukahaji Kecamatan Singaparna Kabupaten Tasikmalaya tentang model pembelajaran inovatif, sehingga terbuka pikiran dan kompetensi serta motivasi dalam diri mereka untuk memiliki kemampuan dalam menguasai berbagai model pembelajaran yang inovatif . Metode yang digunakan dalam kegiatan ini adalah berupa pelatihan melalui ceramah, tanya jawab dan diskusi. Hasil yang dicapai adalah peningkatan pemahaman dan pengetahuan guru-guru MGMP IPS mengenai model pembelajaran inovatif serta cara mengaplikasikan model inovatif tersebut.